Comparison of self-stigma and quality of life in patients with depressive disorders and schizophrenia spectrum disorders – a cross-sectional study - Holubova M; Prasko J; Matousek S; Latalova K; Marackova M; Vrbova K; Grambal A; Slepecky M; Zatkova M (Neuropsychiatric Disease and Treatment)
Michaela Holubova,1,2 Jan Prasko,1 Stanislav Matousek,1 Klara Latalova,1 Marketa Marackova,1 Kristyna Vrbova,1 Aleš Grambal,1 Milos Slepecky,3 Marta Zatkova3 1Department of Psychiatry, Faculty of Medicine and Dentistry, Palacky University Olomouc, University Hospital Olomouc, Olomouc, 2Department of Psychiatry, Hospital Liberec, Liberec, Czech Republic; 3Department of Psychology Sciences, Faculty of Social Science and Health Care, Constantine the Philosopher University in Nitra, Nitra, Slovak Republic Background: The views of one’s self-stigma and quality of life (QoL) in patients with schizophrenia and depressive disorders are significant subjective notions, both being proven to affect patient’s functioning in life. The objective of this study was to investigate the QoL and self-stigma in connection with demographic factors and compare the two groups of patients in terms of those variables. Methods: In a cross-sectional study, the outpatients with schizophrenia spectrum disorders and depressive disorders completed the Quality of Life Satisfaction and Enjoyment Questionnaire, the Internalized Stigma of Mental Illness Scale, and a demographic questionnaire during a routine psychiatric control. Furthermore, both patients and their psychiatrists evaluated the severity of the disorder by Clinical Global Impression-Severity scale. Results: The QoL of patients with depressive disorders or schizophrenia spectrum disorders did not significantly differ between the two groups. In both groups, unemployment was perceived to be a significant factor decreasing the QoL. Self-stigma was detected to be higher in patients with schizophrenia spectrum disorders than in patients with depressive disorders. A strong correlation was found between the two scales, meaning that those with higher levels of self-stigmatization were less prone to see their life as fulfilling and joyful. Conclusion: This study shows that the degree of the internalized stigma can be an important aspect linked to the QoL irrespective of the diagnostic category. Keywords: self-stigma, quality of life, depressive disorders, schizophrenia spectrum disorders